Fluoride release and surface roughness of a new glass ionomer cement: glass carbomer - LOPES,Célia Maria Condeixa de França (2018)
Abstract Objective This study analyzed the fluoride release/recharge and surface roughness of glass carbomer compared to other encapsulated glass ionomer cements (GICs). Material and method The GICs tested were Glass Fill® (GC-GCP Dental), Riva Self Cure® (RS-SDI), Riva Light Cure® (RL-SDI), Equia Fil® (EF-GC Europe). The composite resin Luna® (LU-SDI) was used as control. Five samples of each material were prepared and kept in a humidifier for 24 hours (37 °C, 100% relative humidity). Fluoride release was measured in two times: before (T1: days 1, 2, 7, 14) and after topical application of fluoride (T2: days 15, 16, 21 and 28). The surface roughness was also measured in both times (T1: days 1 and 14; T2: days 15 and 28). All samples were submitted to a single topical application of acidulated fluoride phosphate (Fluor Care - FGM). Two-way ANOVA with repeated measures and Tukey's post-test (p <0.05) were used in the statistical analysis. Result Equia Fil presented the highest fluoride release in both evaluation periods, with a higher release in T1 (p <0.05). The other materials tested, including glass carbomer presented similar release in both periods (T1 and T2). Regarding surface roughness, no significant differences were observed in the interaction between the material × time factors (T1 and T2) (p=0.966). Conclusion The GICs tested presented fluoride release and recharge ability and showed no surface roughness increase by topical application of fluoride.